Ahmadiyah: Analisis Terhadap Teologi dan Perkembangan - Tarhan, Raden Muhammad; Abdullah (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
Ahmadiyya is a phenomenon of renewal of Islamic thought in India with theological characteristics that include it. This article aims to explore the theological concepts proposed by the Ahmadiyya and trace their development. This analysis was carried out through a literature study with a social perspective approach. Based on this study, it can be concluded that the emergence of Ahmadiyya was the result of the thoughts of figures who tried to actualize religious teachings through social understanding and context. This research also shows that Ahmadiyya is a sect in Islam that emerged as a response to the challenges and socio-religious dynamics of its time.